Introductory electrical engineering with math explained in accessible language - Urbano, Magno (Wiley, 2020)
"This book teaches the basics of electrical engineering and explains the underlying mathematics involved using examples that allow the reader to grasp the theory along with the mathematics. The author explains the math theory needed to understand every topic. He includes all math knowledge needed to understand the book. The book incorporates several math tricks and knowledge, such as matrices determinant and multiplication, and how certain formulas are derived. The book also includes tables of integrals and Laplace Transforms and other tables to help the reader to, for example, find resistor's and capacitor's values. The author utilizes twenty-five years in the educational field to provide the reader with accessible language, examples and images to make things easy"- Resumé vydatel